Shaping gender-stereotypical beliefs: The roleof parents and peers - Michela Carlana; Lucia Corno (Institute for Fiscal Studies (IFS), 2022)
We use a lab-in-the-field experiment to explore the influence of parents and peers in shaping adolescents' beliefs on whether they are better in male-typed fields (math) versus female-typed fields (literature). We find that thinking about parental recommendation affects students' beliefs on their comparative advantage in math with respect to literature in a gender-stereotypical way: conditional on ability, girls are 33% more likely to think they are better in literature when they expect their mothers to recommend it, and boys are 15% more likely to think they are better in math when they expect their fathers to recommend it. Our results also show that while peers do not influence boys' beliefs on their comparative advantage, girls are less confident in their relative ability in math compared to literature when they must interact with male students in areas outside their gender's domain.
Keywords: 330; gender stereotypes; parents; peers; comparative advantage; math; literature